Diagnóstico energético del bloque 16 de repsol, mediante el uso de la norma iso 50001 en el año 2015. Propuesta de mejora de la eficiencia energética. - Portilla Bastidas, Franklin Fernando (2017)
In the present work it is developed in Repsol, referring to artificial lift equipment they are EMPLOYEES to extract oil Equipment Water Injection Training which are used to inject formation water obtained from the separation process oil is, formation water and gas; and transportation of crude oil which are used to transport oil. . It is proposed to make energy balances , energy reviews applications and energy consumption in each systems Repsol then develop energy indicators that meet the quality requirements of the ISO 50001 standard and obtain certification of ISO 50001 allows demonstrate commitment and continuous improvement in energy management.